Efektifitas Aplikasi Smart Monitoring Of Maternal (S-Mom) untuk Meningkatkan Kewaspadaan Ibu Hamil Terhadap Tanda Bahaya Kehamilan: Efektifitas Aplikasi Smart Monitoring Of Maternal (S-Mom) untuk Meningkatkan Kewaspadaan Ibu Hamil Terhadap Tanda Bahaya Kehamilan - Nessi Meilan; Eryando, Tris (Universitas Airlangga, 2026)
Backgrounds. Eight hundred thirty mothers in the world die every day due to complications of pregnancy and childbirth. Direct caused are 75% because of bleeding, 24% by high blood pressure during pregnancy (preeclampsia), infection, or prolonged or obstructed labor. Other cause of maternal death is low awareness and the delay in recognizing danger signs during pregnancy, late decision-making caused the mother to be late in reaching a health facility, and the impact was being late for further health intervention. The Government relied on the MCH book, which was revised in 2024, but still provides one-way communication, which is easily damaged and impractical. The classical method must be accompanied by learning videos or MHealth technology, for example, in the form of health applications to increase mother awarness of pregnancy danger signs. Objectives. This research is a pilot test to measure usser acceptanse of S-MOM Application, determine the effectiveness of the S-MOM Application in improving awareness pegnancy danger signs and mother adherence to check danger signs of pregnancy using S-MOM aplication. Method.. This research used a quasi-experimental design, the sample for the quasi-test (35) and quasi-control (35) groups. The researcher used data from the questionnaire to compare the differences in using the MCH book and the S-MOM application. Results. On the Usser Acceptance Test, pregnant women and midwives rated the S-MOM application with the majority reporting